Eco-intensity analysis for a chip-fuelled boiler house - Blumberga, Dagnija; Vīgants, Edgars; Veidenbergs, Ivars; Vīgants, Ģirts; Vītoliņš, Valdis (Journal of Environmental Engineering and Landscape Management, 2012)
The operational eco-intensity of a heat supply system is dependent upon the interaction of its elements and their common performance. It is of special importance to gain insight into possibilities to reduce chip fuel consumption in the case when an additional element – a gas condenser – is installed in a boiler house. The efficiency of a system’s operation is estimated by its eco-intensity; such estimates concern the influence exerted by technological parameters on the reduction in natural resource consumption, allowing this problem to be thoroughly analysed by means of definite factors promoting the eco-intensity rise. Based on the results of commercial experiment, the authors have found the independent variables for the case of gas condenser without packing. The eco-intensity of a boiler house operation decreases as the outdoor temperature falls and therefore the boiler’s load should be increased. This aspect could be due to several causes, among which the most important are: the deviations of the operating parameters of the gas condenser, the increase in the flue gas velocity, and temperature. Analytical treatment of the influence exerted by a boiler’s specific load on the operational efficiency of its energy has shown that as this former grows, the efficiency decreases and therefore less heat energy could be derived from the gas condenser. This should be taken into account at simulation of the control over a gas condenser’s operation. Article in English. Ekologinio intesyvumo namą šildant skiedromis analizė Santrauka. Ekologinis intensyvumas priklauso nuo šilumos tiekimo sistemos elementų sąveikos ir jų bendro veikimo. Tai ypač svarbu tiriant galimybes sumažinti skiedrų kuro sąnaudas tuo atveju, kai šildomame name yra įdiegtas papildomas elementas – dujų kondensatorius. Sistemos veikimo efektyvumas įvertinamas pagal jos ekologinį intensyvumą; tokie vertinimai susiję su įtaka technologiniams parametrams mažinant gamtinių išteklių naudojimą. Remdamiesi tyrimo duomenimis, autoriai nustatė nepriklausomuosius dujų kondensatoriaus kintamuosius. Šildomo namo ekologinis intensyvumas susijęs su lauko temperatūra. Kai ji nukrinta, apkrova turėtų būti padidinama. Tai lemia kelios priežastys, iš jų svarbiausios: dujų kondensatoriaus darbinių parametrų nuokrypiai, išmetamųjų dujų greičio padidėjimas ir temperatūra. Atlikta analizė parodė, kad didinant katilo formą, sistemos efektyvumas mažėja, ir todėl mažiau šilumos energijos tiekiama iš dujų kondensatoriaus. Tai turėtų būti įtraukta į dujų kondensatoriaus veikimo kontrolės modeliavimo skaičiavimus. Reikšminiai žodžiai: dujų kondensatorius, skiedromis šildomas namas, šilumos tiekimo sistema, optimizacija, ekologinis intensyvumas, komerciniai tyrimai, aplinkos tausojimas